2007
DOI: 10.1080/14622200601083541
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of sociocultural factors and young adults' smoking in two midwestern communities

Abstract: Young adults were the only age group to defy the downward trend in cigarette use seen in the 1980s and 1990s. To help explain this phenomenon, we conducted an exploratory study to examine the association between the sociocultural contexts of young adults' everyday lives and their smoking attitudes and behaviors. "Context" was operationalized by (a) including students and nonstudents in the study population, and (b) selecting two distinctly different areas of Minnesota for examination. The study sites were Hibb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…One study found that 30% of young adults not enrolled in college (or without a college degree) smoked, compared to 14% of their college-educated counterparts (36). The study also found differences in smoking prevalence between white-collar and blue-collar workers within the STW population; those employed in the service industry and blue-collar occupations reported the highest rate of smoking prevalence among young adults aged 18 to 24, consistent with other studies (37,38). According to the US Census Bureau's 2006-2008 American Community Survey, approximately 41% of the nearly 30 million young adults aged 18 to 24 are currently enrolled in postsecondary education (39); thus, approximately 18 million young adults in the United States must be in the STW population or military (39).…”
Section: Discussionsupporting
confidence: 90%
“…One study found that 30% of young adults not enrolled in college (or without a college degree) smoked, compared to 14% of their college-educated counterparts (36). The study also found differences in smoking prevalence between white-collar and blue-collar workers within the STW population; those employed in the service industry and blue-collar occupations reported the highest rate of smoking prevalence among young adults aged 18 to 24, consistent with other studies (37,38). According to the US Census Bureau's 2006-2008 American Community Survey, approximately 41% of the nearly 30 million young adults aged 18 to 24 are currently enrolled in postsecondary education (39); thus, approximately 18 million young adults in the United States must be in the STW population or military (39).…”
Section: Discussionsupporting
confidence: 90%
“…In 2009 the percentage of the male population using tobacco was about 29%, with the highest value in the age range 25-44. The main increase was observed in adolescents and young adults [ISS, 2009], as reported in several countries [Warren et al, 2000;Petersen et al, 2003;Gilpin et al, 2005;Steele et al, 2007]. An overall hypothesis that the work environment might influence aspects of smoking behaviour was extensively reported [Albertsen et al, 2006].…”
Section: Discussionmentioning
confidence: 53%
“…Research has indicated that the previous popular hypothesis, which suggests that oral hygiene is the pivotal cause of periodontitis, should be questioned and that smoking may be a more important aetiological factor, especially among developing countries (Peto 1992, Prayitno et al 1993, Amarasena et al 2002, Hujoel 2003. Moreover, cigarette smoking in many countries has exhibited an alarming increase among adolescents and young adults (Warren et al 2000, Gilpin et al 2005, Peterson et al 2006, Steele et al 2007). Periodontal disease is primarily prevalent among the adult population; however, researchers have indicated that this disease is also common and of importance among young adults, adolescents and even children (Bimstein et al 2001).…”
Section: Discussionmentioning
confidence: 99%